THE ROLE OF FORMAL EDUCATION IN SHAPING STUDENTS’ CHARACTER AT SMK SWASTA TELADAN TANAH JAWA: A CASE ON CHARACTER EDUCATION - Herman, Herman; Purba, Ridwin; Silalahi, Dumaris E.; Sinaga, Juli Antasari Br.; Sinaga, Yanti Kristina; Panjaitan, Muktar B.; Purba, Lydia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
It is not simple to develop a child's character. Formal education combined with a good value planting method can help students learn more effectively and shape their personalities. Families, schools, communities, government, and the media all share responsibilities for children's education and character development. The family is the first and most important environment in which children's personalities are formed. The formation of personality Education in schools is an important element of the school's efforts to meet parents' expectations of developing, moulding, and establishing excellent character in their children. Integration and synergy between education in the home (informal) and education at school are required to build and develop children's character (formal). The combination of informal and formal education is hoped to build a good character for students’ especially for the human resources. As we know that Indonesian is rich of natural resources while the human resource’s aspect is a problem. The problem can be solved by enhancing the character of strong human capital based on the Indonesian nation's character through various forms of education (formal, informal, and non-formal) and at various levels of education (ranging from primary, secondary, and tertiary education).